Waves energy in motion (California : AIMS Multimedia [production company] ; [S.l.] : New Era Learning Media [distributor], 1997)
This CD-ROM offers a complete science curriculum. This program contains a complete 25-minute video, random access interactive browsing, interactive quiz, test with record keeping, interactive glossary, teacher management system.
Keywords: Wave mechanics; Physics